Language of Translated Version of ‘Abstract Thought: An Onion' - Adhikari, Bal Ram; Magarati, Shyam Lal (English Language Teaching Perspectives, 2022)
Translation as writing across languages and cultures is characterized by its own linguistic features. Translation researchers have discerned certain linguistic features of translated texts that render the translated language distinct from non-translated one. In this context, the present paper examines the language of Abstract Thought: An Onion, the English translation of Shankar Lamichhane's Nepali essay 'Yābstyrakṭ Chintan: Pyāj' rendered by Govinda Raj Bhattarai. The data were collected and analyzed through qualitative document analysis and the findings are discussed under three thematic headings like lexical borrowing, lexical explicitation and syntactic parallelism. The findings show obligatory and strategic lexical borrowings, explicitation, and syntactic parallelism as the key linguistic features of this Nepali essay in English translation, signaling the translator's fidelity to the source text and his concern for the intelligibility of the translated text. Finally, the study points out the implication of these findings for translation teaching and training.